Protein metabolism in noncranial politrauma patients fasted or fed high protein-energy diet - Teixeira, U. A. [UNESP]; Tsuji, H. [UNESP]; Angeleli, A. Y.O. [UNESP]; Bicudo, M. H. [UNESP]; Burini, R. C. [UNESP] (My University, 1996)
The effect of early-feeding on the protein status of trauma patients was investigated in six males (25-37 yrs old) with noncranial politrauma, ISS 35-45. The study began (2-9 days after the injury) with a 21 hour fasting state (M0) followed by two 3-day periods (M1 and M2) of enterally feeding a complete liquid diet of 1.9g protein - 47 kcal/kg/d. Blood samples and urine were collected throughout the experiment for homones (insulin, C-peptide, Cortisol, glucagon and catecholamines), acute-phase (APP) positive (C-reactive protein, α1-antitrypsin and ceruloplasmin) and negative (transferrin, transthyretin and retinol binding protein) proteins and whole-body protein metabolism (N-balance and 15N-glycine kinetics) analysis. At the begining (M0) the patients showed high levels of APP+, low levels of APP-, along with negative N-balance (-23,6 g/d), high Nflux and high protein catabolism (46g N/9h). The enterai feeding (M0 x M1 = M2) increased the plasma insulin (16x31 uIU/ml), improved the N-balance (M, = -3,5; M2= -5,2 g/d), and reduced the flux by decreasing protein catabolism (M1=27; M2 = 26g N/9h). At the end of the study (M2), the patients still manifested inflammatory activity (APP+/APP-), high hormone (insulin, cortisol and dopamine) levels, and negative N-balance Thus, the present results suggest early feeding as a nutritional procedure for decreasing the protein metabolism of these patients.